Alkali Metal Carbenoids: A Case of Higher Stability of the Heavier Congeners. (21st April 2016) - Molitor, Sebastian; Gessner, Viktoria H.
Abstract: As a result of the increased polarity of the metal–carbon bond when going down the group of the periodic table, the heavier alkali metal organyl compounds are generally more reactive and less stable than their lithium congeners. We now report a reverse trend for alkali metal carbenoids. Simple substitution of lithium by the heavier metals (Na, K) results in a significant stabilization of these usually highly reactive compounds. This allows their isolation and handling at room temperature and the first structure elucidation of sodium and potassium carbenoids. The control of stability was used to control reactivity and selectivity. Hence, the Na and K carbenoids act as selective carbene‐transfer reagents, whereas the more labile lithium systems give rise to product mixtures. Additional fine tuning of the M−C interaction by means of crown ether addition further allows for control of the stability and reactivity.